Work Communication and Work Ethics on Employee Performance and Job Satisfaction - Muhamad Effendi; Dheo Rimbano; Irma Idayati; Gunadi; Muhammad Rahman (PT FORMOSA CENDEKIA GLOBAL, 2023)
The purpose of this study was to find out: (a) How does work communication affect employee job satisfaction, (b) How does work communicationaffect employee performance, (c) How does work ethics affect employee performance, (d) How does job satisfaction affect employee work performance. The method used in this study is the System Literature Review (SLR), which is a term used to refer to a particular research methodology or research and development carried out to collect and evaluate research related to a specific topic focus. The results of the study also prove that work communication affects employee job satisfaction, work communication affects employee performance, work ethics have an impact on employee performance, and job satisfaction has an effect on employee performance.